Assessment of cytotoxicity and genomic instability induced by coal-derived nanoparticles in V79 and HaCaT Cells - Alvaro Miranda-Guevara; Wilner Martínez-López; Grethel León-Mejía; Ornella Fiorillo Moreno; Leonardo Pacheco-Londoño; Julian Rodríguez Tapia; Fredy Jose Torres Cantillo; Maria Fernanda Palma; Paola Hernández; Pablo Liddle; Burix Mechoso; Miriam López; et al. (Archives of Toxicology, 2026)
Coal is a major global energy resource, but its extraction raises significant environmental and health concerns. Mining activities release large amounts of particulate matter, including nanoparticles (NPs), into the environment. These NPs are hazardous due to their content of polycyclic aromatic hydrocarbons (PAHs), metals, oxides, and other compounds capable of disrupting cellular and molecular processes. This study evaluated the cytotoxic and genotoxic effects of coal-derived NPs on V79 and HaCaT cell lines, focusing on their impact on DNA stability and the mechanisms responsible for cellular damage. NPs were isolated using an acid-based separation method and applied to cells at concentrations of 50, 150, and 300 μg/mL. Atomic force microscopy (AFM) provided topographical characterization, while dynamic light scattering (DLS) confirmed their tendency to agglomerate. Scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS) confirmed NP morphology and elemental composition, including carbon, oxygen, iron, calcium, silicon, aluminum, and copper. Cytotoxicity was assessed using resazurin and sulforhodamine B assays, and genotoxicity was evaluated using the comet assay, micronucleus test, and γH2AX immunostaining. Results showed a clear dose-dependent effect, with coal NPs inducing genomic instability and increased cell mortality, mainly through apoptosis. These findings highlight the importance of characterizing coal-derived NPs to better assess their environmental and health risks, particularly regarding respiratory diseases.

dSTORM microscopy evidences in HeLa cells clustered and scattered γH2AX nanofoci sensitive to ATM, DNA-PK, and ATR kinase inhibitors - Pablo Liddle; Jorge Jara-Wilde; Laura Lafon-Hughes; Iván Castro; Steffen Härtel; Gustavo Folle (Molecular and Cellular Biochemistry, 2020)

Bleomycin-induced γH2AX foci map preferentially to replicating domains in CHO9 interphase nuclei - Pablo Liddle; Laura Lafon-Hughes; María Vittoria Di Tomaso; Ana Laura Reyes-Ábalos; Jorge Jara; Mauricio Cerda; Steffen Härtel; Gustavo A. Folle (Chromosome Research, 2014)

Preferential localization of γH2AX foci in euchromatin of retina rod cells after DNA damage induction - Laura Lafon-Hughes; María Vittoria Di Tomaso; Pablo Liddle; Andrea Toledo; Ana Laura Reyes-Ábalos; Gustavo A. Folle (Chromosome Research, 2013)